Influence of Bionic Non-smooth Surface on Water Flow in Antiskid Tire Tread Pattern - 王国林 周海超 杨建 梁晨 金梁 (东华大学学报（英文版）, 2013)
Inspired by the idea that bionic non-smooth surfaces （BNSS） can reduce water flow resistance,the application of BNSS resistance reduction method in grooves surface of antiskid tire tread pattern has been investigated for increasing hydroplaning velocity of tire by using computational fluid dynamics （CFD） simulation.Three kinds of BNSS （riblet,convex dome,and dimple concave） are arranged in tire tread grooves to study the water flow resistance effects in grooves with non-smooth characteristics.A tire-water coupled model is established and CFD technique is applied to simulating hydroplaning.The simulation results show that BNSS grooves can reduce water flow resistance and increase mean flow rate by disturbing the eddy movement in boundary layers.The drag forces of riblet and dimple surface are lower and drainage capacity is higher than those of smooth surface under the same void space on tread pattern,but it is not in dome.BNSS is a good way to promote antiskid performance without increasing additional groove space;extra tire-road noise production is therefore avoided due to groove space enlargement.